The amazing spider-man (2022), volume 5, part 1 ebook Dead language. - Wells, Zeb (Amazing Spider-Man (2022), 2023)
Collects Amazing Spider-Man (2022) #19-23. Amazing answers to your burning questions! What did Peter Parker do that ruined Spider-Man's reputation?! What happened all those months ago between Peter and Mary Jane Watson? What does the immediate future have in store for both of them? And who is the creepy-looking figure that has something to do with all of it? The answers will be worth the wait! Plus: DARK WEB is over, but the fallout will haunt Spider-Man for a long time. To recover, Peter and Felicia Hardy, A.K.A. the Black Cat, escape from the city to an exclusive spa in the Catskills! Surely nobody will ruin their romantic getaway by trying to kill them - right?